An expert panel on the adequacy of safety data and physiological roles of dietary bovine osteopontin in infancy - Fleming, Stephen A.; Reyes, Sarah M.; Donovan, Sharon M.; Hernell, Olle; Jiang, Rulan; Lönnerdal, Bo; Neu, Josef; Steinman, Lawrence; Sørensen, Esben S.; West, Christina E.; Kleinman, Ronald; Wallingford, John C. (Frontiers in Nutrition, 2024)
Human milk, due to its unique composition, is the optimal standard for infant nutrition.Osteopontin (OPN) is abundant in human milk but not bovine milk. The addition of bovine milk osteopontin (bmOPN) to formula may replicate OPN's concentration and function in human milk.To address safety concerns, we convened an expert panel to assess the adequacy of safety data and physiological roles of dietary bmOPN in infancy. The exposure of breastfed infants to human milk OPN (hmOPN) has been well-characterized and decreases markedly over the first 6 months of lactation. Dietary bmOPN is resistant to gastric and intestinal digestion, absorbed and cleared from circulation within 8-24 h, and represents a small portion (<5%) of total plasma OPN. Label studies on hmOPN suggest that after 3 h, intact or digested OPN is absorbed into carcass (62%), small intestine (23%), stomach (5%), and small intestinal perfusate (4%), with <2% each found in the cecum, liver, brain, heart, and spleen. Although the results are heterogenous with respect to bmOPN's physiologic impact, no adverse impacts have been reported across growth, gastrointestinal, immune, or brain-related outcomes. Recombinant bovine and human forms demonstrate similar absorption in plasma as bmOPN, as well as effects on cognition and immunity.The panel recommended prioritization of trials measuring a comprehensive set of clinically relevant outcomes on immunity and cognition to confirm the safety of bmOPN over that of further research on its absorption, distribution, metabolism, and excretion. This review offers expert consensus on the adequacy of data available to assess the safety of bmOPN for use in infant formula, aiding evidence-based decisions on the formulation of infant formula.